Aporetic Belonging: Thinking the Experience of Buddhist-Christian Practice with Gillian Rose - McDermott, Chris (Buddhist Christian studies, 2024)
The possibility of authentic Buddhist-Christian belonging and practice has largely been affirmed or dismissed on the basis of the individual participant's different understandings of their respective faith traditions. Here, I suggest that the philosopher Gillian Rose's speculative thought offers a complimentary lens through which to engage in the conversation, particularly those themes imbricated in her speculative thinking around the broken middle, inaugurated mourning, or "working through," recognition, and appropriation. A different kind of dialogue emerges from her thinking that refocuses engagement from merely being a presentation of different views to a humanizing and deeper regard for dialogue partners across their differences, with implications for wider interreligious encounters and peacebuilding.